2022
DOI: 10.3390/ijerph191911992
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Nationwide COVID-19 Risk in Mexico through the Lens of Comorbidity by an XGBoost-Based Logistic Regression Model

Abstract: The outbreak of the new COVID-19 disease is a serious health problem that has affected a large part of the world population, especially older adults and people who suffer from a previous comorbidity. In this work, we proposed a classifier model that allows for deciding whether or not a patient might suffer from the COVID-19 disease, considering spatio-temporal variables, physical characteristics of the patients and the presence of previous diseases. We used XGBoost to maximize the likelihood function of the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Similarly, studies in Mexico have reported that diabetes and pneumonia increase the risk of COVID-19 in both adult and older populations [2,39]. They also report that obesity and smoking increase the risk of COVID-19 [2,39]. However, our study shows that hypertension increases the risk of COVID-19, unlike other studies conducted on the Mexican population [2].…”
Section: Comorbidities and Their Association With Covid-19supporting
confidence: 51%
See 1 more Smart Citation
“…Similarly, studies in Mexico have reported that diabetes and pneumonia increase the risk of COVID-19 in both adult and older populations [2,39]. They also report that obesity and smoking increase the risk of COVID-19 [2,39]. However, our study shows that hypertension increases the risk of COVID-19, unlike other studies conducted on the Mexican population [2].…”
Section: Comorbidities and Their Association With Covid-19supporting
confidence: 51%
“…In our study population, type 2 diabetes, hypertension, and respiratory diseases were associated with an increased risk of developing COVID-19. Similarly, studies in Mexico have reported that diabetes and pneumonia increase the risk of COVID-19 in both adult and older populations [2,39]. They also report that obesity and smoking increase the risk of COVID-19 [2,39].…”
Section: Comorbidities and Their Association With Covid-19mentioning
confidence: 89%
“…In our model, asthma lowered the probability 1.09-fold of COVID-19 fatality, possibly related to glucocorticoid asthma treatments available over the counter in Mexico. Other analyses of COVID-19 mortality in Mexico have reported reduced risk of hospitalisation among asthmatics [ 27 ], or no significant effect of asthma on mortality [ 39 ]. A systematic review and meta-analysis of 62 studies that included 2 457 205 individuals found a reduced risk of mortality among individuals with asthma [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Latin America continues to a high burden of active COVID-19 cases. [4][5][6] Most COVID-19 infected individuals recover without the need for specialized medical care, and many do not exhibit any symptoms. 7,8 The severity of the disease is modulated by coexisting medical disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Over 200,000,000 individuals, or roughly 75% of the world's population, have gotten at least one dose of a vaccination 2,3 . Latin America continues to a high burden of active COVID‐19 cases 4‐6 …”
Section: Introductionmentioning
confidence: 99%